The role of orthodontists in the multidisciplinary management of obstructive sleep apnea - Jorge Faber; Aliciane Mota; Lai-In Ho; M Ali Darendeliler (SpringerOpen, 2024)
Abstract Background Obstructive sleep apnea (OSA) is a complex disorder characterized by interruptions in breathing during sleep, leading to a range of adverse outcomes from reduced quality of life to serious health risks, including cardiovascular diseases and increased mortality. Main Body This manuscript reviews the orthodontists' essential role in the multidisciplinary healthcare team tasked with managing OSA. It particularly highlights critical orthodontic interventions, such as surgical-orthodontic maxillomandibular advancement (MMA), mandibular advancement appliances (MAAs), and rapid maxillary expansion (RME). These interventions are pivotal in modifying craniofacial structures to enhance airway patency. The importance of conducting a thorough airway analysis is underscored, assessing the complete anatomical and functional factors contributing to airway obstruction. Conclusion The paper calls for increased collaborative research efforts to develop standardized, evidence-based orthodontic procedures for effectively managing OSA, aiming to improve patient outcomes through specialized, tailored interventions.